Fractionation and Characterization of Seed Storage Proteins from Different Wheat Varieties Cultivated in Sindh on SDS-PAGE Electrophoresis - Khan, Shaista; Memon, A.N.; Ghanghro, Allah Bux; Tahir, Ibtessam (Pakistan Journal of Nutrition, 2011)
Wheat is most widely cultivated cereal and important source of food and protein worldwide. Wheat is a staple diet containing most of the ingredient, for wide range of food. The unique property of wheat flour is to form dough and this property is due to gluten required for making preparation of chapatti and bread. Fractionation and characterization of seed storage proteins of fourteen wheat varieties cultivated in sindh was carried out by Sodium Dodecyle Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE). Wheat grains of fourteen (14) varieties were collected from different region of sindh (Pakistan). Electrogram of each variety were calculated by Jaccard’s Similarity Index (JSI). Genetic diversity of different sindh wheat varieties was measured by constructing dendogram of High Molecular Weight (HMW) and Low Molecular Weight (LMW) gluten sub unit bands. The dendrogram profile data showed the variation in the number and position of bands from one variety to the other, while some bands are common.